Determinants of Takeover Success in the UK: A Discriminant Analysis - Nakkeeran, Nandhinie (2012)
In this thesis report, I explore the possible determinants for takeover success with a sample of 418 bids made during the period 2007 – 2011 in the UK (United Kingdom). The purpose of this thesis is to identify the most significant determinants that predict takeover success. The results from the empirical test using discriminant analysis reveal that competition among bidders and target attitude are the most significant factors determining outcome of takeover. Both have a negative impact on takeover success. Cross-border is a significant factor and negatively contributes to takeover success. Cross-industry and payment method are moderately significant in predicting the outcome of takeover. Cross-industry has a negative impact and payment method has a positive impact on takeover success. Bid premium has a positive impact on takeover success but it’s not significant enough to influence takeover success.